(3GdYhGUe hGdbhGSe aj GdPH Yf SfI CHj GdbGSes - (3eMeO Hf EHQGgje Hf Ydj Hf GdeQJVj Hf GdeaVd GdMSfj GdbGSej, CHh YHO Gddg, YR GdOjf, ef Bd GdhRjQ,J (B840 (3g` s
(3ChdgG (B:s
(3Gdhge GdKGef hGdYTQhf s
(3BNQgG (B:s
(3BNQg eHJhQ , hGdehLhO efg CKfGA aUd (B: (3ai GdeLGR GdeLeY Ydjg , bhdg (B: (3hEfeG jMJGL Edi Gdage GdUMjM Hjf eNJdaGJ GdCOdI s
[ (3GdfUa GdKGfi (B]s
(3hbO SHb GdcJGH JQLeI ddeUfa Hbde CHfg HebOGQ (B19 (3hQbIs
(3cJHJ GdYfGhjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds